Morphometrics and Growth Patterns of Squids in the North and South Coasts of Java, Indonesia - Ervinia, Ayu; Simanjuntak, Charles P H; Sulistiono, Sulistiono; Wulandari, Dwi Yuni; Zairion, Zairion (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Highlight Research The mitre squid (Uroteuthis chinensis), the Indian squid (Uroteuthis duvaucelii), and the purpleback flying squid (Sthenoteuthis oualaniensis) were identified. Morphometric differences among three squid species were analyzed. Microanatomy observations on the shapes of the sucker rings were important for species identification. Hypoallometric and isometric growth patterns were observed. Abstract Squids play vital ecological and economic functions as keystone species in marine food webs and integral components of global capture fisheries. However, a comprehensive understanding of their diversity and life history characteristics in Indonesian waters is still poorly understood. This study aimed to identify squids that inhabited Java's northern and southern coasts and examine their growth pattern through morphometric analysis. Six hundred eighteen squid samples were collected fishers caught from May to September 2022 in Blanakan and Palabuhanratu Bay, representing two areas of interest. The body size and the shape of sucker rings of squids were observed using morphometric method. Kruskall-Wallis test, Principal Component Analysis, and Spearman's correlation were performed to investigate morphometric variation and relationships. The length-weight relationships were estimated for each species.. This study reported three species of squid on the north and south coasts of Java, namely the mitre squid (Uroteuthis chinensis), the Indian squid (Uroteuthis duvaucelii), and the purpleback flying squid (Sthenoteuthis oualaniensis). There were significant differences observed in ten morphometric variables among the three species of squid (p < 0.05), with fin width, fin length, and sucker ring teeth identified as the key distinguishing feature for the squids. Spearman's correlation indicated stronger associations between mantle and fin variables (Ï = 0.666-0.967, p < 0.05) than those between mantle and head variables (Ï = 0.380-0.864, p < 0.05).Mantle length-weight relationships revealed a hypoallometric growth pattern for U. chinensis and U. duvaucelii, while S. oualaniensis exhibited an isometric growth pattern. The finding of this study provides valuable insights concerning the growth of squids that reflect variation in ontogenic development, trophic ecology, and environmental conditions in Indonesian waters.